Grounded Action - Odis Simmons; Toni A. Gregory (Grounded Theory Review: An International Journal)
Grounded action is the application and extension of grounded theory for the purpose of designing and implementing practical actions such as interventions, program designs, action models, social and organizational policies, and change initiatives. Grounded action is grounded theory with an added action component in which actions are systematically derived from a systematically derived explanatory grounded theory. Actions are grounded in the grounded theory in the same way that grounded theories are grounded in data. Grounded action was designed by the authors to address complex, multi-dimensional organizational and social problems and issues.